2018
DOI: 10.1155/2018/6354680
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Loss of Mitochondrial Function in Epithelial Tissue Can Be Reversed by Coenzyme Q10

Abstract: The process of aging is characterized by the increase of age-associated disorders as well as severe diseases. Due to their role in the oxidative phosphorylation and thus the production of ATP which is crucial for many cellular processes, one reason for this could be found in the mitochondria. The accumulation of reactive oxygen species damaged mitochondrial DNA and proteins can induce mitochondrial dysfunction within the electron transport chain. According to the “mitochondrial theory of aging,” understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 39 publications
0
25
0
2
Order By: Relevance
“…All correlations seen between the neuropsychological tests and MMP were no longer significant after controlling for age, education and brain reserve. Age, years of education and brain reserve can potentially confound the correlations between neuropsychological measurements and the fibroblast metabolic markers, as all three factors have been shown to affect either performance on neuropsychological tests [39,40] or mitochondrial function [41]. To control for the effect of these three covariates, a further analysis was performed taking these parameters into account.…”
Section: Neuropsychological/metabolic Correlationsmentioning
confidence: 99%
“…All correlations seen between the neuropsychological tests and MMP were no longer significant after controlling for age, education and brain reserve. Age, years of education and brain reserve can potentially confound the correlations between neuropsychological measurements and the fibroblast metabolic markers, as all three factors have been shown to affect either performance on neuropsychological tests [39,40] or mitochondrial function [41]. To control for the effect of these three covariates, a further analysis was performed taking these parameters into account.…”
Section: Neuropsychological/metabolic Correlationsmentioning
confidence: 99%
“…The fact that the mitochondrial electron transport chain is the major ROS production site makes mitochondria the key target of oxidative damage. Therefore, the mitochondrial aging theory is associated with the free radical theory [15,47].…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro studies have reported the effects of ALA in rat cell cultures [ 41 , 42 ] and CoQ10 in human cells [ 43 , 44 ], consistently showing decreased ROS production and inflammation, as well as an increase in thiol production and an improvement in ETC. Polyphenols can exert antioxidant or prooxidant effects depending on the oxygen and glucose levels used in the cell culture.…”
Section: Basic Research Studiesmentioning
confidence: 99%